Peran Dikmas Lantas Melalui Kegiatan Police Goes to Factory dalam Mencegah Pelanggaran Lalu Lintas di Wilayah Hukum Polres Cianjur - Siburian, Radot (Advances in Police Science Research Journal, 2019)
Increasing the number of vehicles in Indonesia raises various kinds of problems, one of which is traffic violations. The results of the data obtained by the author that the increase in traffic violations is dominated by private employees. Based on letter (d) of Article 62 of the National Police Chief Regulation Number 23 of 2010, the Dikyasa Unit has the responsibility to implement the Dikmas Lantas, in this study, to private employees. Therefore, a study was conducted aimed at obtaining a picture of the implementation of the Dikmas Lantas on private employees, analyzing the role of the Dikmas Lantas, and describing the factors that influenced the Dikmas Lantas. The theory that the author uses in this study is based on management theory by George R. Terry, role theory by Sarwono, and communication theory by Lasswell. For the concept that is, the concept of community education then, the concept of traffic violations, the concept of employees, the concept of traffic and road transportation and the operational guidelines for the Police Chief Police Number: Juklak / 05 / V / 2003 concerning Community Education in the Field of Traffic. The approach used by the authors in this study is a qualitative approach and the method used is descriptive analysis. The sources used are primary, secondary and tertiary sources. Data collection techniques used in this study were interviews, observation and document review. The findings obtained by the authors during the study that there has been an increase in traffic violations in the last 3 years among private employees. The unit is believed to have made a pre-emptive effort including providing Dikmas Lantas through police goes to factory activities. From the results of the study also found inhibiting factors regarding the number of personnel who are not in accordance with DSP, lack of competence of members because they have not followed Dikjur, law enforcers who still give wrong examples, facilities and infrastructure, budgets, lack of awareness of private employees, sectoral communication and communication on institutions other. The author's advice in this paper is to add personnel in accordance with the DSP (List of personnel arrangements) and coaching members through education, improvement of facilities and infrastructure and supporting budgets, collaborating with companies in Cianjur Regency, making orderly cadres in traffic in each company. Keywords: Role, Dikmas Lantas, Police goes to factory, Traffic Violations by Private Employees